Curricular Guidelines for Rural Education in the state of Mato Grosso: a view from the Natural Sciences - Ilma Ferreira Machado Machado; Valdenir de Souza Coutinho (Universidade Federal do Norte do Tocantins, 2022)
This article aims to analyze how the rural education curriculum is approached in the Curricular Orientations of Basic Education of the state of Mato Grosso and how the theoretical-methodological propositions presented here can be articulated by Natural Sciences. The study is guided by a critical conception of education and by a qualitative research methodology, based on the analysis of documents on Rural Education, in particular the Curricular Orientations of Basic Education of the state of Mato Grosso, in the section where the question of Rural Education is addressed. The results of the research show that the pedagogical indications made in the curricular orientations safeguard the specificities of rural schools and make great contributions to Natural Sciences. It is important that the political-pedagogical projects indicate study topics and actions that dialogue with the reality of the rural world and with the socio-cultural, environmental and productive knowledge of rural workers, so that the natural sciences can act significantly in the formation of the students.